Preparation of Proper Culture Medium for Saccharomyces cerevisiae var. boulardii with Molasses and Animal Serum - Mahdi Salimi; Mohamadreza Mahzonieh (Pasteur Institute of Iran, 2015)
Introduction: The purpose of this study was formulation and preparation of a proper culture medium for Saccharomyces cerevisiae var. boulardii with molasses and animal serum. Methods: A fully-crossed factorial design contain 5%, 10% and 20% of molasses (M) with 0, 1% and 5% animal serum (S) was used in this study. The pH of all culture medias were adjusted to 5.6 with acetic acid. The seed was consisted of 106 yeast particles which was added to culture media. The inoculated medias were incubated at 37°C for 48 h and the mean yeast counts was recorded. Results: The mean of yeast counts for 5% M+0% S, 5% M+1% S, 5% M+5% S, 10% M+0% S, 10% M+1% S, 10% M+5% S, 20% M+0% S, 20% M+1% S, 20% M+5% S were 273333±20033, 228666±34428, 317333±170485, 499333±100425, 516000±38314, 514666±107057, 499333±100425, 516000±38314 and 514666±107057 particles in ml, respectively. In order to optimize culture medium, vitamins and vitamins in combination with minerals (at a concentration of 0.5%) were added to the optimal concentration of molasses and serum. Conclusion: Statistical analysis with ANOVA test showed that the growth rate of yeast in 10% molasses plus 1% serum had a significant difference with 5% and 10% molasses in solid medium or 5% molasses supplemented with 1% serum (p< 0.05). The addition of vitamins and minerals did not yield significant growth. Therefore, it can be concluded that the combination of molasses and serum may be able to provide basic requirements of the yeast S. cerevisiae var. boulardii.